Structural and optical properties of ZnO nanoparticles prepared by direct precipitation method - Kahouli, M.; Barhoumi, A.; Bouzid, Anis; Al-Hajry, A.; Guermazi, S. (Superlattices and microstructures, 2015)
•High quality of synthesized ZnO powder with hexagonal wurtzite structure.•ZnO nanoparticles exhibit a broad band at about 369nm in the absorption spectra which is characteristic of a pure ZnO.•Raman studies indicate first and second order active modes of the ZnO. ZnO nanoparticles were synthesized by direct precipitation method at ambient conditions. Structural, thermal, morphological and optical properties of ZnO nanoparticles were investigated by X-ray diffraction (XRD), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), Ultraviolet–Visible spectroscopy and Raman spectroscopy. The XRD measurement shows that ZnO powder has a wurtzite structure. The grain size was estimated from Scherer’s method and Williamson–Hall (W–H) plots. From DSC curve we can deduce the various endothermic and exothermic peaks obtained when the sample was heated from room temperature to 413°C. The morphology and grain distribution of ZnO nanoparticles were analyzed by SEM. Optical properties were investigated by UV–Visible spectroscopy. The Tauc model was used to determine the optical gap energy of the synthesized ZnO particles. The observed Raman peak at 438cm−1 was attributed to the E2 (high) mode. The broad band at 569cm−1 is due to disorder-activated Raman scattering for A1 mode. These bands are associated with the first-order Raman active modes of the ZnO phase.